Impact of a pilot pathway for the management of gastroenteritis‐like symptoms in an emergency department: A case study following a Salmonella outbreak. (17th November 2015) - Ranse, Jamie; Luther, Matt; Ranse, Kristen
Abstract: Objective: This research aims to describe the effect of standard care (control) versus a clinical management pathway (intervention) on patient length of stay and admission rates during a public health emergency at one Australian ED. Methods: A retrospective audit of hospital records for patients who presented in May 2013 with gastroenteritis‐like symptoms was undertaken following a surge in patient presentations from a Salmonella outbreak. Patients who presented with gastroenteritis‐like symptoms between 15 and 19 May 2013 received care according to a clinical management pathway (intervention). The focus of the intervention was based on symptom management, including a standardised approach to analgesia, anti‐emetics and rehydration. Patient characteristics, such as age and gender are described using descriptive statistics. A Mann–Whitney test was used to compare continuous data, and a Fisher's exact test was used to compare categorical data, between the two groups. Results: Over an 8 day period, 110 patients presented with gastroenteritis‐like symptoms. The median length of stay was statistically different between the two groups ( P < 0.001). More patients were admitted to hospital from the control group ( n = 5) when compared with the intervention group ( n = 0); however, given the small number of patients in these groups, inferential statistical analysis was not a reasonable consideration. Conclusion: The length of stay for patients between the two groups was statistically different, suggesting that the implementation of a clinical management pathway for patients with gastroenteritis‐like symptoms reduced the ED length of stay. This finding is useful in future planning for similar public health emergency responses and/or for use when patients present with gastroenteritis‐like symptoms on a daily basis.